Entrenching Democracy and Good Governance: The Role of ICT - Adesola, S.A. (Richtmann Publishing, 2012)
With the rapid spread of Information and Communication Technologies (ICTs), new opportunities havebeen opened for a revival of public discourse and improved governance efficiency. ICTs offer concreteopportunities for local and national governments to improve their performance in terms of transparency,participation and decentralization. The mainstreaming of ICTs within planning and design of developmentstrategies helps to strengthen the establishment of efficient, effective and transparent governance systems.This paper takes a critical look at Democracy and Governance. What constitute Good Governance was alsoitemized. The role of ICT in entrenching Democracy and Good Governance was also discussed. Finally,conclusion was drawn and recommendations for way forward were given.